Fundamentals of management text and Philippine cases - Rodriguez, Rafael A.; Echanis, Erlinda S. (Diwata Publishing, 1997)
The changes in the third edition involve the updating of examples and illustrations, as well as data in various tables in Chapter 3. A section on business reengineering and on new control measures were added in Chapter 8 and 15, respectively, to cover two management issues which have received considerable attention in the business literature in recent years.